68Ga-PSMA ligand PET/CT in patients with prostate cancer: How we review and report. Issue 1 (December 2016) - Rauscher, Isabel; Maurer, Tobias; Fendler, Wolfgang; Sommer, Wieland; Schwaiger, Markus; Eiber, Matthias
Abstract Recently, positron emission tomography (PET) imaging using PSMA-ligands has gained high attention as a promising new radiotracer in patients with prostate cancer (PC). Several studies promise accurate staging of primary prostate cancer and restaging after biochemical recurrence with68 Ga-PSMA ligand Positron emission tomography/computed tomography (PET/CT). However, prospective trials and clinical guidelines for this new technique are still missing. Therefore, we summarized our experience with68 Ga-PSMA ligand PET/CT examinations in patients with primary PC and biochemical recurrence. It focuses on the technical and logistical aspects of68 Ga-PSMA ligand PET/CT examination as well as on the specific background for image reading discussing also potential pitfalls. Further, it includes relevant issues on free-text as well as structured reporting used in daily clinical routine.